The Effectiveness of Group Guidance Services in Improving Students Self-Confidence in Junior High School - Arte, Reno Mutiara; Syukur, Yarmis (Universitas Negeri Padang, 2025)
This research aims to analyze the effectiveness of group guidance services in improving students' self-confidence at SMPN 4 Lubuk Alung. This research used a quantitative approach with a one-group pretest–posttest pre-experimental design. The research was conducted at SMPN 4 Lubuk Alung in the 2024/2025 academic year. Participants were 11 students (aged 13–14 years; 4 boys, 6 girls) in grades VII and VIIII, selected through purposive sampling technique based on the initial identification of students with low self-confidence levels. The intervention was carried out in 3 group guidance meetings, each lasting 30–40 minutes. The research instrument was a self-confidence questionnaire consisting of 38 items with a Likert scale of 1–5, covering three main dimensions: self-esteem, competence, and belonging. Data analysis was performed using the Wilcoxon signed-rank test. All students showed an increase in self-confidence scores after participating in group guidance services. The Wilcoxon test yielded a Z value of -2.934 with p = 0.003 (p < 0.05), indicating a significant difference between the pretest and posttest scores. It can be concluded that group guidance services have been proven effective in improving the self-confidence of junior high school students. These findings recommend the implementation of structured group services as an intervention strategy to develop self-confidence in adolescents in the school environment.